Applying Ibn ʿArabī's Concept of Tajallī: A Sufi Approach to Environmental Ethics - Bambang Irawan; Ismail Fahmi Arrauf Nasution; Hywel Coleman (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2021)
This article examines the Sufi concept of tajallī and its application to environmental ethics. This study usesdescriptive and productive interpretation to analyze the data which are extracted from the main works of Ibn ͑Arabī, namely Fuṣūṣ al-Ḥikam and al-Futūḥāt al-Makkiyya. It finds that Ibn ʿArabī’s concept of tajallī can be understood not only in its philosophical sense but also in its spiritual and moral sense to develop a new approach to environmental ethics. This research has valid implications for taking a new direction in the study of mystic Islam and environmental ethic by incorporating tajallī and other Sufi doctrines such as waḥdat al-wujūd, maḥabbah, and maʿrifah.